A Long-Term Geothermal Observatory Across Subseafloor Gas Hydrates, IODP Hole U1364A, Cascadia Accretionary Prism - Becker, Keir; Davis, Earl E.; Heesemann, Martin; Collins, John A.; McGuire, Jeffrey J. (Frontiers in Earth Science, 2020)
We report four years of temperature profiles collected from May 2014 to May 2018 in Integrated Ocean Drilling Program (IODP) Hole U1364A in the frontal accretionary prism of the Cascadia subduction zone. The temperature data extend to depths of nearly 300 meters below seafloor (mbsf), spanning the gas hydrate stability zone at the location and a clear bottom-simulating reflector at ~230 mbsf. When the hole was drilled in 2010, a pressure-monitoring Advanced CORK (ACORK) observatory was installed, sealed at the bottom by a bridge plug and cement below 302 mbsf. In May 2014, a temperature profile was collected by lowering a CTD down the hole from the ROV ROPOS. From July 2016 through May 2018, temperature data were collected during a nearly two-year deployment of a 24-thermistor cable installed to 268 m below seafloor (mbsf). The cable and a seismic-tilt instrument package also deployed in 2016 were connected to the Ocean Networks Canada (ONC) NEPTUNE cabled observatory in June of 2017, after which the thermistor temperatures were logged by ONC at one-minute intervals until failure of the main ethernet switch in the integrated seafloor control unit in May 2018. The thermistor array had been designed with concentrated vertical spacing around the BSR and two pressure-monitoring screens at 203 and 244 mbsf, with wider thermistor spacing elsewhere to document the geothermal state up to seafloor. The four years of data show a generally linear temperature gradient of 0.055°C/m consistent with a heat flux of 61-64 mW/m2. The data show possible evidence for very slow upward advection of pore fluids at up to 10-10 m/s, but no indication of any other transients in the formation. In-situ temperatures are ~15.8°C at the BSR position, consistent with methane hydrate stability at that depth and pressure.